WEB SITE RELIABILITY ANALYSIS USING THE PYTHON PARSING METHOD (Journal of Universal Science Research, 2024)
This article discusses methods for analyzing the reliability of a Web site using the parsing method based on the Python language. A generalized reliability analysis algorithm is presented that allows you to assess the quality and stability of the functioning of a website. The algorithm is based on parsing structural elements of the page, such as HTML tags, links , text blocks, and analysis of their state and contents. To implement the algorithm, a Python program was developed that is capable of automatically analyzing a selected website and identifying potential problems. The experiment showed the effectiveness and accuracy of the developed approach, which allows it to be used for systematic monitoring and increasing the reliability of websites.